numint - udot(2) = L/2*(u(4).^2.*sin(u(3)) -...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
function udot=numint(t,u) f L = 1; g = 9.81; g udot(3) = u(4); udot(1) = u(2); udot(4) = u(2).*sin(u(3)).*u(4)/2/L - (g*sin(u(3))/2 +udot(2).*cos(u(3)))/L;
Background image of page 1
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: udot(2) = L/2*(u(4).^2.*sin(u(3)) - udot(4).*cos(u(3))); udot = udot'; u return...
View Full Document

This document was uploaded on 10/24/2010.

Ask a homework question - tutors are online